Preventative health assessments and indigenous people of Australia: a scoping review - Kim Usher; Kim Usher; Debra Jackson; Humayun Kabir; Humayun Kabir; Rikki Jones; Joe Miller; Rachel Peake; Reakeeta Smallwood (Frontiers Media S.A., 2023)
Given that Indigenous populations globally are impacted by similar colonial global legacies, their health and other disaprities are usually worse than non-indigenous people. Indigenous peoples of Australia have been seriously impacted by colonial legacies and as a result, their health has negatively been affected. If Indigenous health and wellbeing are to be promoted within the existing Australian health services, a clear understanding of what preventive health means for Indigenous peoples is needed. The aim of this scoping review was to explore the available literature on the uptake/engagement in health assessments or health checks by Indigenous Australian peoples and to determine the enablers and barriers and of health assessment/check uptake/engagement. Specifically, we aimed to: investigate the available evidence reporting the uptake/engagement of health checks/assessments for Australian Indigenous; assess the quality of the available evidence on indigenous health checks/assessments; and identify the enablers or barriers affecting Indigenous persons' engagement and access to health assessment/health checks. A systematic search of online databases (such as Cinhl, Scopus, ProQuest health and medicine, PubMed, informit, google scholar and google) identified 10 eligible publications on Indigenous preventive health assessments. Reflexive thematic analysis identified three major themes on preventive health assessments: (1) uptake/engagement; (2) benefits and limitations; and (3) enablers and barriers. Findings revealed that Indigenous peoples' uptake and/or engagement in health assessments/check is a holistic concept varied by cultural factors, gender identity, geographical locations (living in regional and remote areas), and Indigenous clinical leadership/staff's motivational capacity. Overall, the results indicate that there has been improving rates of uptake of health assessments by some sections of Indigenous communities. However, there is clearly room for improvement, both for aboriginal men and women and those living in regional and remote areas. In addition, barriers to uptake of health asessments were identified as length of time required for the assessment, intrusive or sensitive questions and shame, and lack of access to health services for some. Indigenous clinical leadership is needed to improve services and encourage Indigenous people to participate in routine health assessments.